Contrast Echocardiography for the Detection of a Giant Right Coronary Artery Aneurysm: A Useful Diagnostic Tool - De Rosa, Fabrizio; Rabia, Granit (Journal of Cardiology and Cardiovascular Medicine, 2024)
Coronary artery aneurysm is an uncommon condition defined as abnormal dilatation of the coronary artery. We report the case of a man admitted to the Emergency Department for suspected intestinal obstruction. At abdominal/thoracic Computed Tomography (CT) it was reported a suspected pericardial cyst. Contrast echocardiography showed a clear pattern of blood flow inside the mass with a probable origin at a very limited region where it was also possible to sample an ECG-synchronized system-diastolic Pulse-Wave (PW)-Doppler pattern, typical for a coronary artery flow. Our suspicion of a giant coronary artery aneurysm was then confirmed by coronary CT and coronary angiography. The patient was transferred to a Cardiac Surgery center where he underwent surgical treatment for the aneurysm. Most coronary aneurysms are clinically silent and are often incidentally detected. Coronary angiography is the ‘‘gold standard’’ for diagnosis and evaluation of coronary artery aneurysms. Among non-invasive diagnostic techniques, Computed Tomography Coronary Angiography is the best method for coronary artery anatomy and coronary abnormalities. However, echocardiography with the use of a contrast agent, a cost-effective non-radiation nature, and a widespread use method, maybe a reliable method to detect and characterize the masses, allowing a differential diagnosis. Learning objective 1. Recognition and evaluation of cardiac masses require first-line imaging methods such as echocardiography. 2. The use of additional non-invasive (cardiac CT or MRI) and/or invasive imaging methods are often required. 3. Contrast echocardiography may be helpful, as second-line imaging methods, to better characterize the mass and approach the correct diagnosis.